1995
DOI: 10.1093/oxfordjournals.aje.a117668
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Maternal Age Differences in Birth Weight

Abstract: The authors studied three hypothesized explanations for reduced birth weights of infants born to US adolescent mothers--social disadvantage, biologic immaturity, and unhealthy behaviors during pregnancy. A hierarchical regression analysis was pursued to evaluate these explanations using data from the National Longitudinal Study of Youth on 1,754 first births between 1979 and 1983 to women aged 14-25 years at the time of birth. The birth weights of infants of mothers aged 14-17, 18-19, and 20-23 years were 133,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
2
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 0 publications
8
61
2
4
Order By: Relevance
“…The birth measurements of the infants of the two group of women were similar and a significant difference was only seen in the mid-upper arm circumference and the triceps skinfold thickness. The finding of similar birth weight between the groups in this study was different from previously reported studies, where the adolescent group had lower birth weights (Naeye, 1981;Fraser et al, 1995;Strobino et al, 1995;Thame et al, 1999;Conde-Agudelo et al, 2005). Thame et al (1999) reported that adolescents had infants with birth weights 200 g less than their mature counterpart.…”
Section: Discussioncontrasting
confidence: 99%
“…The birth measurements of the infants of the two group of women were similar and a significant difference was only seen in the mid-upper arm circumference and the triceps skinfold thickness. The finding of similar birth weight between the groups in this study was different from previously reported studies, where the adolescent group had lower birth weights (Naeye, 1981;Fraser et al, 1995;Strobino et al, 1995;Thame et al, 1999;Conde-Agudelo et al, 2005). Thame et al (1999) reported that adolescents had infants with birth weights 200 g less than their mature counterpart.…”
Section: Discussioncontrasting
confidence: 99%
“…Younger maternal age is associated with being unmarried, primiparous and under-educated, alcohol/substance abuse, heavy smoking and inadequate prenatal care, which may lead to adverse pregnancy outcomes (2,(16)(17)(18)(19)(20)(21)(22). Young mothers may also be more likely to have a pregnancy due to sexual abuse compared with adult mothers, which could lead to an impaired stress response or to variable behaviors that increase the likelihood of preterm delivery (22).…”
Section: Discussionmentioning
confidence: 99%
“…Young maternal age has usually been considered a high risk in relation to adverse pregnancy outcomes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Possible explanations for adverse pregnancy outcomes have been thought to be their biological immaturity or poor social, economic and behavioral factors such as smoking, alcohol/substance abuse, malnutrition and inadequate prenatal care (17)(18)(19)(20)(21)(22). However, the previous studies had conflicting findings regarding whether the effect of young maternal age on adverse pregnancy outcomes were caused by their biological immaturity or poor social, economic and behavioral factors (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…11 Social factors, such as ethnicity, poverty status, age at menarche, maternal height, and net maternal weight gain have an independent effect on birth weight in adolescent mothers. 12 Maternal weight at birth, low pre-pregnancy weight, and poor weight gain during pregnancy are positively associated with increase in FGR. 13,14 Women with lower socioeconomic status commonly have poor nutritional status, maternal anaemia, and poor prenatal care and substance abuse problem, which affect foetal growth.…”
Section: Maternal Factorsmentioning
confidence: 96%